A Fixed Point Result in a Double Control Metric Space Setting and a Fredholm Integral Equation (European Journal of Pure and Applied Mathematics, 2025)
In this present work, we prove a fixed point result for generalized contraction mappings in the setting of a double control metric space (DCMS) by using α-orbital admissibility. The uniqueness of the fixed point is established by adding further hypotheses. The presented result is supported by a concrete example. Moreover, we ensure the existence of a solution of a Fredholm type integral equation via a fixed point technique. Some consequences are also presented to make effective the obtained results.